Equilibrium, kinetic and thermodynamic study for the efficient removal of pentachloronitrobenzene from aqueous solution by an activated carbon derived from Pinus ponderosa - Gulen, Jale; Cesmeli, Cisel; Ozturk, Bilal (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2025)
Activated carbon has been synthesised from Pinus Ponderosa shell and used for adsorption of pentachloronitrobenzene. Initial pesticide concentration, initial pH of the solution and phases contact time are the investigated parameters. The equilibrium is attained in 20 and 30 min for diluted specimens (1 and 3.5 mg/L) and 75 min for concentrated specimens (6.5 and 9 mg/L). Linear, Langmuir and Freundlich isotherm models are applied to the experimental data. The maximum monolayer adsorption capacity is found at approximately 350 mg/g from the Langmuir model. This value of the novel carbonized adsorbent can be compared to the adsorption capacities of other materials. The kinetics of adsorption is analyzed via pseudo-first and second-order models. High Regression coefficients and the closeness of the calculated and experimental capacity values are found for pseudo first order model kinetic. The Gibbs energy shows the feasible and spontaneous adsorption. The activation energy and surface coverage relationship are evaluated by sticking probability factor. The results show that the pesticide was removed by the physical type adsorption mechanism and also good binding characteristic on the activated adsorbent.
Keywords: Active carbon; Isotherms; Kinetic; Pesticide removal; Thermodynamic parameter; LOW-COST ADSORBENT; BAGASSE FLY-ASH; METHYLENE-BLUE; WASTE-WATER; CARBOFURAN PESTICIDES; ADSORPTION; MECHANISM; SORPTION; BIOCHAR; DYE; Chemistry; Engineering